2012
DOI: 10.3923/ajpp.2012.135.142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic and Mineral Soil Fertilization on Essential Oil of Spilanthes oleracea cv. Jambuarana

Abstract: In the present study, the composition of essential oil of leaves and inflorescences of jambu (Spilanthes oleracea . Jambuarana), under organic manuring and mineral fertilization, was studied. Jambu plants show important chemical properties and their production has been addressed for the extraction of the essential oils for cosmetics industries, due to their pharmacological properties. The experimental area of treatments contained urea as mineral fertilizer (120 g m2), applied twice and organic fertilizer (8 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
0
7
0
8
Order By: Relevance
“…Organic fertilization of jambu also influences the content of plant phytochemical compounds. Borges et al (2012) observed increases of 31.6% in the content of spilantol and 16.8% of flavonoids in inflorescence, compared to conventional fertilization. Organic fertilizer induced higher levels of total phenolics, carotenoids, spermidine, and spermine in leaves and flowers of jambu than under conventional cultivation (Borges et al, 2016).There are various recommendations of organic fertilization for vegetable production; however, to define more precise doses, information, such as soil analysis, history of the place to be fertilized, and type of organic fertilization, are required.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Organic fertilization of jambu also influences the content of plant phytochemical compounds. Borges et al (2012) observed increases of 31.6% in the content of spilantol and 16.8% of flavonoids in inflorescence, compared to conventional fertilization. Organic fertilizer induced higher levels of total phenolics, carotenoids, spermidine, and spermine in leaves and flowers of jambu than under conventional cultivation (Borges et al, 2016).There are various recommendations of organic fertilization for vegetable production; however, to define more precise doses, information, such as soil analysis, history of the place to be fertilized, and type of organic fertilization, are required.…”
Section: Introductionmentioning
confidence: 75%
“…The jambu plant (Acmella oleracea L.) is a leaf vegetable, widely consumed in the northern Brazilian region as a seasoning and medicinal herb. Its flavor is quite peculiar, its flowers producing a sensation of tingling and torpidity of the mouth mucosa, due to the presence of spilanthol (Borges et al, 2012;Borges et al, 2014). In the state of Pará, jambu is cultivated by periurban producers in small areas, together with other seasoning and leaf vegetables, such as coriander, lettuce, and chives, especially to sustain the consumption of the city of Belém and the main urban centers of the northeastern mesoregion of the state (Homma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An important chemical property of the plant has aroused the interest of the pharmaceutical industry, due to the presence of the active ingredient known as spilanthol (Borges et al, 2012). Spilanthol is an alkylamide with several plant protection bioactivities, because it has antibacterial, antifungal and analgesic action (Veryser et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Jambuarana, apresenta um total de 66 substâncias químicas (BORGES et al, 2014). Segundo Borges et al, (2013) e Borges et al, (2012) dentre essas substâncias, tem-se o espilantol, trans-cariofileno, germacreno D, L-dodeceno e espatulenol, características bioquímicas essas que vem atraindo a atenção de empresas farmacêuticas e de cosméticos para as plantas de jambu.…”
Section: Composição Química Do Jambuunclassified